Análisis de sostenibilidad en Radio Surcos 97.5 FM en el cantón Guaranda, provincia Bolívar, año 2018 - Lema Cuji, Danny Patricio (2019)
The investigation was conducted for the purpose of determining whether Radio Surcos 97.5 FM has implemented policies of balanced sustainability in the economic, social, technological, political, legal and environmental aspects that allow them to assure their continuity and positioning and can last in time. The type of study for the collection of the information was the application of field research, which allowed to have an integral perspective of the problematic raised, In the investigation the inhabitants of the urban and rural zone of the Guaranda canton participated, by means of statistical calculations a sample of 73 inhabitants of Guaranda was determined, the instruments for the obtaining of the data of the citizenship the survey was applied and for the obtaining of the data of the company the interview was applied that was directed to the director of the Radio Surcos. The results obtained show that Radio Surcos is an institution that belongs to the Diocese of Guaranda; however, it operates autonomously since its main income comes from the commercial part, specifically from the agreements that the workers make with the commercial houses of the locality and the subscription of contracts with advertising agencies of the country, which serves to cover the expenses of the personnel and the operating expenses of the institution. In conclusion, Radio Surcos is one of the most tuned stations in the city of Guaranda and day by day the administration is optimistic that the station will become one of the most consolidated radio institutions in the local market. Keywords: Development, sustainability, strategies, growth, communication, indicators.